Hubungan Konsumsi Pangan dan Aktivitas Fisik dengan Status Gizi Remaja di SMA Inklusif Galuh Handayani Surabaya - Galuh Ariantika; Rahayu Dewi Soeyono (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Health problems that generally occur in adolescents are excess and underweight, where the nutritional status figures do not reach normal according to standards. As for these problems, the causative factors are identified, such as food consumption and physical activity factors. From the available data, there is still little research devoted to adolescents who have special conditions (disabilities). This study aims to determine the relationship between food consumption and physical activity with the nutritional status of adolescents, so that it can be ascertained that the most important factors for normal nutritional status are achieved. This research is a type of correlational quantitative research and was carried out at the Galuh Handayani Inclusive High School, Surabaya. The research subjects were adolescents with various disabilities, totaling 17 students. The independent variables in the study were food consumption and physical activity, while the dependent variable was nutritional status. The instruments used include 2 x 24 Food Recall and Physical Activity Questionnaire for Adolescents. To determine the relationship between variables, then analyzed using Spearman's rank correlation. The results of the analysis showed that there was a significant relationship between food consumption (P = 0.025) and nutritional status and the correlation coefficient value was 0.540 which resulted in a strong correlation, but there was no significant relationship between Physical Activity (P = 0.133) and the nutritional status of adolescents at Galuh Handayani Inclusive High School Surabaya with a correlation coefficient value of 0.380 which means that the correlation is sufficient.There is a significant relationship between food consumption and nutritional status, but there is no significant relationship between physical activity and the nutritional status of adolescents at Galuh Handayani Inclusive High School, Surabaya